The Intellectual Characteristics of Early Qing Confucian Christians: A Review of “The Convergence and Divergence of Heaven and Confucianism: A Study of Early Qing Confucian Christians” - LIU, Rumeng (Journal of Research for Christianity in China (JRCC), 2025)
This review examines the book Heaven and Confucianism: A Study of Early Qing Confucian Christians (hereafter referred to as Heaven and Confucianism). By analyzing the author’s research on the biographical details, social networks, and faith worlds of representative early Qing Confucian Christians, the reviewer summarizes the fundamental ideological characteristics of these early Qing Confucian Christians. The review also addresses the author’s classification of early Qing Confucian Christians and their overall characteristics.